IbM BAGI KELOMPOK PENGRAJIN PEMBUAT PERALATAN DAPUR DI DESA KEPATIHAN TULUNGAGUNG JAWA TIMUR - Rulirianto Rulirianto; Bambang Irawan; Heru Utomo (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2016)
Kitchen Appliance maker Craftsmen group is a group of productive people who daily make kitchen tools such as the cormorant, pots, pans, bread oven, stove. In the course of production using very basic equipment and even many of these self-made equipment. Manually production activities and acquired skills passed down from their parents.Implementation Activities IbM with the  introduction of production techniques by means of "Heating", particularly metal goods (metal plate) needs to be done in order to more easily molded material as required, especially in the manufacture of products guttering or else that needs welding. Aluminum material more easily formed with the correct tools and patient so that the corner of the tray, resulting in better grooves and smooth and has as weet look.The need for marketing knowledge, then the seller will be more wise and prudent and painstaking in serving the prospective buyer or the buyer of goods. Besides, the placement of goods neater (Layout), as well as the need for acquisition of knowledge about the product being sold. Marketing to traditional markets by way of consignment or storage of goods.